Pengaruh Label Halal dan Celebrity Endorser terhadap Keputusan Pembelian (Survei pada Konsumen Wardah di Ponorogo) - Premi Wahyu Widyaningrum (JESI (Jurnal Ekonomi Syariah Indonesia), 2016)
Increasing public awareness in the running of living according Islamic religious rules, this affects consumer buying behavior. Consumers become selective in buying non food and food products with regards halal label. Promotion strategies are applied producers of halal products for positive impact of advertising messages can be delivered is primarily to use celebrities who have religious impression on her. The objective of this study is to analyze and explain the effect of halal label and celebrity endroses toward  Purchase Decision. The research belongs to explanatory research. The samples are taken by using systematic random sampling. The size of samples determined 30  people. Population in this study is customers wardah who studied Muhammadiyah University of Ponorogo. Empirical data was collected through survey methodology. Data has been analyzed through Generalized Structured Component Analysis (GSCA).  The findings of the study show: 1) Halal label significantly effect on Purchase Decision 2) Celebrity Endorser significantly effect on Purchase Decision. Limitations: The data for the study has been collected through one cluster only. However for the purpose of generalization insights from other significant clusters should be collected. The study should be replicated in other cities of the country to have more indiscriminate findings.